Clinical characteristics of bimaxillary protrusion in different population/ Naili Hayati Abdul Mukti ... [et al.] - Abdul Mukti, Naili Hayati; Noviaranny, Indah Yuri; Venkiteswaran, Annapurny; Abdul Ghani, Sarah Haniza (Faculty of Dentistry, 2017)
In this paper, we discussed the characteristic of bimaxillary protrusion in different population. We also incorporated about aetiology and management of bimaxillary protrusion. It is importance to understand the characteristics of skeletal and dental of bimaxillary protrusions in a specific population, in order to decide whether to treat by orthodontic camouflage only, or combination with orthognathic surgery and orthodontics.